2019
DOI: 10.1002/ar.24315
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned from the developmental origins of childhood renal cancer

Abstract: Despite the rarity of renal tumors in children, many different types of malignant and nonmalignant renal neoplasms have been described. Therefore, the correct diagnosis and clinical management of these patients can represent a challenge. Here we provide a comprehensive review of the commonly diagnosed pediatric renal malignancies, including nephroblastoma (commonly known as Wilms tumor), clear cell sarcoma of the kidney, rhabdoid tumor of the kidney, several subtypes of renal cell tumors (often collectively te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 158 publications
(211 reference statements)
0
9
0
2
Order By: Relevance
“…Fellow collaborator Prof. David Nikolic‐Paterson and colleagues have shown in their review article the key role of apoptosis signal‐regulating kinase 1 (ASK1/MAP3K5) in acute and chronic kidney disease, and its potential as a therapeutic target (Tesch, Ma, & Nikolic‐Paterson, 2020). Rounding out this section is a comprehensive review from Dr. Jason Cain (a former PhD student of John's) on childhood renal malignancies, with an emphasis on their origins and pathological features (Chong & Cain, 2020).…”
Section: Renal Anatomy Physiology and Pathologymentioning
confidence: 99%
“…Fellow collaborator Prof. David Nikolic‐Paterson and colleagues have shown in their review article the key role of apoptosis signal‐regulating kinase 1 (ASK1/MAP3K5) in acute and chronic kidney disease, and its potential as a therapeutic target (Tesch, Ma, & Nikolic‐Paterson, 2020). Rounding out this section is a comprehensive review from Dr. Jason Cain (a former PhD student of John's) on childhood renal malignancies, with an emphasis on their origins and pathological features (Chong & Cain, 2020).…”
Section: Renal Anatomy Physiology and Pathologymentioning
confidence: 99%
“…Macroscópicamente se observa como una masa blanda, única y grande, de color gris pálido, que distorsiona el riñón normal, principalmente localizada en la médula renal y que puede contener quistes, hemorragia y/o necrosis (2,4,8,11). El SCC posee histología muy variable y puede imitar otros tumores renales pediátricos, por lo que su e412 diagnóstico histológico puede resultar muy difícil.…”
Section: Anatomopatologíaunclassified
“…Esto es peligroso al tratarse de una tumoración agresiva, con tendencia a la recurrencia. A pesar de ser una enfermedad generalmente sintomática, caracterizada por dolor abdominal, hipertensión arterial y hematuria, estos síntomas son inespecíficos y se comparten con otros tumores renales (2). A nivel anatomopatológico ha sido un desafío, ya que no presenta un patrón histológico típico; tampoco se cuentan con marcadores inmunohistoquímicos específicos para su diagnóstico (5).…”
Section: Introductionunclassified
“…1,8 With the development of biological technologies, an increasing number of relevant mutated genes have been discovered, among which Wilms tumor 1 (WT1) and catenin beta 1 (CTNNB1) have been consistently confirmed to affect the occurrence and development of Wilms tumor. 9 Furthermore, a genome-wide association study involving European and American patients has also indicated that chromosomes 2p24 and 11q14 are associated with Wilms tumor, whereas chromosomes 22q12, Xp22 and 5q14 are predicted as potential risk regions. 10 In addition, approximately 1-2% of patients with Wilms tumor have a familial hereditary inheritance pattern, and the incidence of Wilms tumor varies significantly among different populations.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few perinatal factors were identified to alter the risk of Wilms tumor in previous studies, including maternal exposure to pesticides, maternal hypertension, gestational age, premature birth, high birth weight and birth order 1,8 . With the development of biological technologies, an increasing number of relevant mutated genes have been discovered, among which Wilms tumor 1 ( WT1 ) and catenin beta 1 ( CTNNB1 ) have been consistently confirmed to affect the occurrence and development of Wilms tumor 9 . Furthermore, a genome‐wide association study involving European and American patients has also indicated that chromosomes 2p24 and 11q14 are associated with Wilms tumor, whereas chromosomes 22q12, Xp22 and 5q14 are predicted as potential risk regions 10 .…”
Section: Introductionmentioning
confidence: 99%